Environmental and Health Impact of Solid Mineral Exploration and Exploitation in South-Northern Nigeria: A Case Study of Igarra in Edo State - Ndinwa, G. C. C; Ohwona, C. O (Review of Environment and Earth Sciences, 2014)
The act of quarrying/mining and the subsequent processing and transporting of these raw materials are greatly hampered by high environmental and health costs. This is observable at the quarry sites, processing factories and the surrounding environments. It is important to state that the environment of the northern part of Edo State has suffered in many areas where exploitation of earth resources by quarrying method and the subsequent processing are carried out. This was revealed from the fieldwork. The importance of these minerals to the nation’s economy cannot be undermined. There is no wisdom therefore to suggest that mining activities be eliminated in order to sustain the quality of the environment. What should be done is for the government, industrial prospectors and environmentalists to take precautionary and remedial measures that can minimize the ill-effects of mineral development. Emphasis should shift to sustainable exploitation of the resources, while the enforcement agency should ensure that quarrying and mining of rocks by the industrial prospectors are in line with the Quarry Act of Nigeria 1979.